2022
DOI: 10.1002/adma.202207688
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hydrophobization Provides Hygroscopic Supramolecular Plastics Based on Polysaccharides with Damage‐Specific Healability and Room‐Temperature Recyclability

Abstract: concern over the global plastic pollution. [1][2][3][4][5][6][7] These supramolecular materials are considered to effectively extend service life and improve recycling rate through readily repairing and reprocessing, which will make significant contribution to realize a sustainable society. [8][9][10][11] Different from the traditional plastics based on extremely stable covalent bonds and crosslinks, supramolecular plastic materials incorporate weak intermolecular interactions such as ionic interactions, [12][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This not only allows the preparation of noncolloidal form self-supporting macroscopic molecular selfassembled materials but also makes it possible to get diversified functions. 23,24,26,[28][29][30]32,33,35 However, we found that the film formation ability and the resultant mechanical strength of the film depend highly on the surfactant and polyelectrolyte structure, in particular, the surfactant chain length and the molecular weight of the PE. In order to reveal the physical insight behind this effect, herein, we report a systematic study of the films formed with sodium alkyl sulfates and poly dimethyl diallyl ammonium chloride (PDDA).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…This not only allows the preparation of noncolloidal form self-supporting macroscopic molecular selfassembled materials but also makes it possible to get diversified functions. 23,24,26,[28][29][30]32,33,35 However, we found that the film formation ability and the resultant mechanical strength of the film depend highly on the surfactant and polyelectrolyte structure, in particular, the surfactant chain length and the molecular weight of the PE. In order to reveal the physical insight behind this effect, herein, we report a systematic study of the films formed with sodium alkyl sulfates and poly dimethyl diallyl ammonium chloride (PDDA).…”
Section: Introductionmentioning
confidence: 85%
“…Under mild mechanical pressure and in the presence of physically adsorbed water to facilitate molecular rearrangement, the caking in the PE/surfactant precipitates leads to a self-supporting supramolecular film, where the surfactant bilayers were bridged by the PE chains to form continuous macroscopic structures. This not only allows the preparation of noncolloidal form self-supporting macroscopic molecular self-assembled materials but also makes it possible to get diversified functions. ,,, ,,, However, we found that the film formation ability and the resultant mechanical strength of the film depend highly on the surfactant and polyelectrolyte structure, in particular, the surfactant chain length and the molecular weight of the PE. In order to reveal the physical insight behind this effect, herein, we report a systematic study of the films formed with sodium alkyl sulfates and poly dimethyl diallyl ammonium chloride (PDDA).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, it improved flexibility. [35] Nevertheless, plastics repaired by hot-pressing exhibited slight improvements in mechanical properties, which was due to further ester exchange reactions and component densification. The re-processability and reparability of supramolecular biomaterials can effectively extend their lifespan and use time, while wastes can be closed-loop recycled, making them more sustainable, as shown in Figure 5f.…”
Section: Manufacture Of Suberin-lignin-cellulose Supramolecular Biopl...mentioning
confidence: 99%
“…[7] In particular, gels often lack recycling performance, which does not meet the needs of sustainable development with the growing concern over global pollution. [8] Covalently crosslinked rigid networks generally fail to be recycled. However, the mechanical properties of the reversible noncovalent bond network are not ideal.…”
Section: Introductionmentioning
confidence: 99%